2012
DOI: 10.1111/j.1570-7458.2012.01254.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between crystalline proteins of two Bacillus thuringiensis strains against Spodoptera exigua

Abstract: The aim of the present article was to evaluate potential synergism between crystalline proteins produced by two Bacillus thuringiensis Berliner strains, MPU B6 and MPU B9, against beet armyworm, Spodoptera exigua (Hübner) (Lepidoptera: Noctuidae). Protein inclusions of bacterial strains were isolated from a spore‐crystal mixture. We estimated the 50% lethal concentration (LC50) of crystals for S. exigua larvae. Insecticidal activity of MPU B6 and MPU B9 individual crystal preparations against caterpillars were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…We determined the pesticidal activity of mixtures of B. thuringiensis MPU B9 crystals with azadirachtin and mustard oil against lepidopteran insects. We chose MPU B9 isolate because of the large number and variety of genes coding for insecticidal toxins (Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ) and the high activity of preparations based on this strain against insects (Konecka et al, , , , ; Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ). Considering the possibility of synthesising by B. thuringiensis factors harmful for vertebrates (Kim et al, ; Mac Innes & Bouwer, ; Mukry et al, ), our research was based on the analysis of the activity of preparations without spores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the pesticidal activity of mixtures of B. thuringiensis MPU B9 crystals with azadirachtin and mustard oil against lepidopteran insects. We chose MPU B9 isolate because of the large number and variety of genes coding for insecticidal toxins (Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ) and the high activity of preparations based on this strain against insects (Konecka et al, , , , ; Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ). Considering the possibility of synthesising by B. thuringiensis factors harmful for vertebrates (Kim et al, ; Mac Innes & Bouwer, ; Mukry et al, ), our research was based on the analysis of the activity of preparations without spores.…”
Section: Discussionmentioning
confidence: 99%
“…The strain was used because of the high number and variety of genes coding for crystalline toxins: cry1Aa , 1B , 1C , 1D , 1I , 2Ab , 9B , 9E (Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ). Preparations based on MPU B9 isolate containing crystals (Konecka, Baranek, Kaznowski, Ziemnicka, & Ziemnicki, ; Konecka, Baranek, Ziemnicka, & Kaznowski, ; Konecka, Hrycak, & Kaznowski, ; Konecka, Ziemnicka, Baranek, & Kaznowski, ) or crystals and spores (Konecka, Kaznowski, Ziemnicka, Ziemnicki, & Paetz, ) showed high insecticidal activity against lepidopteran pests.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation procedure was described previously (Konecka et al 2012(Konecka et al , 2015(Konecka et al , 2019. The strains were cultured on a medium for bacteria sporulation (Lecadet and Dedonder 1971) at 308C for seven days.…”
Section: Isolation Of B Thuringiensis Crystalline Proteinsmentioning
confidence: 99%
“…Moreover, mass spectrometry analysis revealed that MPU B9 crystals contained Cry1Aa, 1Ba, 1Ca, 1D, and 9E toxins (Baranek et al 2017). Bacterial crystals alone or with spores showed high insecticidal activity against insect pests (Konecka et al 2018c(Konecka et al , 2015(Konecka et al , 2012(Konecka et al , 2007b. B. thuringiensis strain MPU B54 harbored the following genes: cry1Aa, cry1Ab, cry1C, cry1D, cry1I, cry2Ab, cry9B, and cry9E.…”
Section: Introductionmentioning
confidence: 99%
“…Some species such as the beet armyworm Spodoptera exigua can survive on transgenic Bt cotton expressing Cry1Ac toxin (Adamczyk et al., ). Spodoptera exigua is a highly polyphagous pest (Smits et al., ) that feed on more than 290 species of plants (Moulton et al., ; Dingha et al., ), including weeds, trees, grasses, legumes, and many field crops globally (Konecka et al., ). Even though Cry1Ac does not kill S. exigua larvae, our results showed that Cry1Ac reduces larval growth at the concentration of 500 to 2000.0 ng/cm 2 by a surface contamination bioassay (Ma et al., ).…”
Section: Introductionmentioning
confidence: 99%